(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
Genetic divergence among population genotypes is useful for understanding the conservation of available genetic resources. The aim of this work was to evaluate the genetic divergence between the genotypes of jabuticaba tree in relation to the phenotypic characteristics of stem length and shoots analyzed in three productive cycles. The genotypes of jabuticaba tree came from the Fruteiras Nativas da Universidade Tecnológica Federal do Paraná – Campus Dois Vizinhos. The genotypes had their origin in forest fragments of the Southwest Region of Paraná and the State of Minas Gerais. Genetic divergence was perform through analysis of variance (ANOVA), Mahalanobis distance, Tocher optimization cluster analysis and by the nearest neighbor method. The results obtained showed that the diversity among the genotypes was alter according to the analysis cycle, because in each one there were the formation of different groups by the methods used. Genotypes from Minas Gerais tended to remain in distinct groups, since it had low similarity with the others. The genotype ’Vitorino’ had a high divergence among individuals from the same place.